Physical training influence on blood pressure dynamics and target organs status in arterial hypertension patients - N. I. Gromnatsky; V. A. Novikov; V. N. Shilenok (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To study physical training (PT) antihypertensive effects and influence on left ventricular (ГУ) structure and function, cerebral blood flow, and endothelial vasokinetic function in patients with arterial hypertension (AH). Material and methods. In total, 74 AH patients were examined at baseline, while receiving two-week indifferent therapy, and then after one-month PT course. PT effectiveness was assessed by 24-hour blood pressure monitoring (BPM). Target organ influence was assessed by echocardiography, transcranial duplex sonography of cerebral vessels, with functional metabolic and myogenic tests, as well as with ultrasound endothelial function assessment. Results. One-month PT was effective as a method of antihypertensive therapy in 47% of the patients. For systolic and diastolic BP, mean daily figures and BP load indices were reduced. PT did not affect TV structure. In patients with antihypertensive PT effect, TV early diastolic filling velocity increased, as well as peripheral resistance indices for intracranial cerebral arteries. Positive dynamics of cerebral blood flow auto-regulation was observed. Fndothelium-dependent vasodilatation improvement was observed in all AH patients, regardless of PT effect, but more significantly in BP reducers. Conclusion. PT effectiveness for systemic BP reduction in Stage I-II AH patients reached 47%. Beneficial PT effects on target organs were more manifested in individuals with greater BP reduction.